Performance analysis of double threshold energy detection-based spectrum sensing in low SNRs over Nakagami-m fading channels with noise uncertainty - Eslami, Amir; Karamzadeh, Saeid (IEEE, 2016)
Cognitive radio is the key technology to overcome the lack of available spectrum in the world that the demand for it is rapidly increasing while people use more wireless services and need higher speeds. One of the key functions of cognitive radio is to ensure that there will be no interference between the primary users and secondary ones by detecting the transmission channel occupation reliably. Because of low computational complexity, energy detection-based (ED) spectrum sensing is very popular. Double threshold energy detection-based (DTED) spectrum sensing is introduced to increase the reliability of normal ED method. In this paper, the performance of DTED spectrum sensing method with the parameters effecting in low SNRs over Nakagami-m fading channels with and without noise uncertainty will be analyzed.